2017
DOI: 10.1002/uog.18543
|View full text |Cite
|
Sign up to set email alerts
|

EP14.27: Outcome comparison of the pregnancies with undetected macrosomia with known macrosomia

Abstract: Electronic poster abstracts respectively. We found no significant difference in gestational age, gender ratio, MCV, red blood cell count, hematocrit, thrombocyte count, INR, and partial thromboplastin time. Conclusions: IUGR is a diagnostic challenge because fetal biometry has a 50% detection rate. Our results show that placental volume is more concordant with birthweight than placental weight. The estimation of placental volume via ultrasound could complete fetal biometry and a. umbilicalis flowmetry in diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Unrecognized FGR may preclude patients from receiving the appropriate antenatal surveillance and potentially increase the risk for stillbirth. Likewise, studies have shown a higher incidence of shoulder dystocia in patients with undiagnosed macrosomia 19 . To avoid such risks, if these findings are reproduced in future studies, obstetrics and gynecology training programs may consider additional training sessions on obtaining fetal biometry in preterm fetuses and in full-term fetuses with high BWs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Unrecognized FGR may preclude patients from receiving the appropriate antenatal surveillance and potentially increase the risk for stillbirth. Likewise, studies have shown a higher incidence of shoulder dystocia in patients with undiagnosed macrosomia 19 . To avoid such risks, if these findings are reproduced in future studies, obstetrics and gynecology training programs may consider additional training sessions on obtaining fetal biometry in preterm fetuses and in full-term fetuses with high BWs.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, studies have shown a higher incidence of shoulder dystocia in patients with undiagnosed macrosomia. 19 To avoid such risks, if these findings are reproduced in future studies, obstetrics and gynecology training programs may consider additional training sessions on obtaining fetal biometry in preterm fetuses and in full-term fetuses with high BWs. Care should also be taken to ensure accurate dating so that EFW measurements and fetal weight percentiles are a true reflection of gestational age.…”
Section: Discussionmentioning
confidence: 99%